Methods for eliciting and measuring behavioral and physiological consequences of stress and uncertainty in virtual reality - Brunyé, Tad T.; Giles, Grace E. (Frontiers in Virtual Reality, 2023)
Military operations are characterized by high levels of stress and uncertainty, and these states can influence cognitive and physical performance outcomes. These states, however, can be difficult to reliably induce in laboratory contexts, making it challenging to quantify and model their influences on perceptual and cognitive processes underlying performance on applied tasks. Herein we describe the development and validation of a novel scenario-based virtual reality methodology, the decision making under uncertainty and stress (DeMUS) scenario, that accomplishes four primary goals. First, it induces physiological and biochemical stress responses through a threat of shock manipulation. Second, it induces transient states of uncertainty by manipulating stimulus clarity in a perceptual decision-making task. Third, it generates several performance metrics regarding recognition memory, spatial orienting, threat classification, and marksmanship decision making. Finally, the task combines behavioral, physiological, and biochemical measures to provide a more comprehensive understanding of how stress and uncertainty influence applied task performance. To provide an initial validation of the scenario and its associated tasks and measures, we conducted a pilot study (N = 18) involving stress induction and cognitive performance assessment. Analyses revealed that: 1) the DeMUS scenario elicited tonic and phasic biochemical (salivary free cortisol) and physiological (heart rate, pupil diameter) stress responses, 2) the scenario elicited variable sympathetic autonomic nervous system (ANS) and hypothalamic-pituitary adrenal (HPA) axis responses, and 3) stress influenced some measures of memory and decision-making in both negative and positive directions. Continuing research will assess individual- and group-level predictors of performance on these virtual reality tasks, and emerging performance enhancement techniques that can help military personnel sustain performance during stressful operations.